2020
DOI: 10.1155/2020/5236236
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA-451a as a Novel Circulating Biomarker for Colorectal Cancer Diagnosis

Abstract: Background. Colorectal cancer (CRC) is one of the leading causes of cancer death worldwide. Successful treatment of CRC relies on accurate early diagnosis, which is currently a challenge due to its complexity and personalized pathologies. Thus, novel molecular biomarkers are needed for early CRC detection. Methods. Gene and microRNA microarray profiling of CRC tissues and miRNA-seq data were analyzed. Candidate microRNA biomarkers were predicted using both CRC-specific network and miRNA-BD tool. Validation ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…The molecule miR-451a has been studied in many types of cancer such as stomach cancer, hepatocellular carcinoma, bladder cancer, colorectal cancer, and basal cell carcinoma. Several studies have suggested that a low expression level of miR-451a positively correlates with the metastatic ability and invasiveness of cancer cells [ 23 , 24 , 25 , 26 , 27 ]. Some studies suggest that miR-451a can be used as a biological marker to predict the risk of recurrence [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecule miR-451a has been studied in many types of cancer such as stomach cancer, hepatocellular carcinoma, bladder cancer, colorectal cancer, and basal cell carcinoma. Several studies have suggested that a low expression level of miR-451a positively correlates with the metastatic ability and invasiveness of cancer cells [ 23 , 24 , 25 , 26 , 27 ]. Some studies suggest that miR-451a can be used as a biological marker to predict the risk of recurrence [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that a low expression level of miR-451a positively correlates with the metastatic ability and invasiveness of cancer cells [ 23 , 24 , 25 , 26 , 27 ]. Some studies suggest that miR-451a can be used as a biological marker to predict the risk of recurrence [ 23 , 24 ]. In the field of TC research, experimental data from multiple cell types have confirmed that miR-451a could suppress tumour cell proliferation and invasion by targeting PSMB8 and ZEB1 [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, both findings indicate a possible role played by this miRNA in the age-associated decline of muscle mass and function characteristic of frailty and sarcopenia. miR-451a is also present in serum, where it can be found either inside vesicles or as non-vesicle associated protein (miRNA-protein, or miRNA-lipid/lipoprotein complexes) [40,[45][46][47][48]. Importantly, when inside vesicles Table 2 Serum miRNAs expression in frail subjects and in robust subjects before and after intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Although miR-451 has not previously been described in the context of IBD, this study revealed it to be permanently increased. The role of miR-451 in cancer has been reported to function by repressing colorectal cancer by inhibiting tumor growth and IL6R expression ( 42 ) and the PI3K/AKT/mTOR signaling pathway ( 43 ), being dysregulated in primary colorectal tumors and in patients' sera ( 44 ). It therefore seems that this miRNA could have opposite functions to those of miR-15b-5p, and a compensatory balance between the 2 miRNAs is probably a biological target of the cells to prevent recurrence, although this hypothesis needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Increased miR-125b-5p levels have been observed when CD4+ T-cell differentiation is inhibited, mainly by targeting interferon-gamma, interleukin-2, and interleukin-10 ( 44 ). This miRNA has also been associated with the inhibition of B-cell activation, the promotion of macrophage activation, and the induction of apoptosis or proliferation through the modulation of p53 expression ( 49 ).…”
Section: Discussionmentioning
confidence: 99%